INTERACTIVE FLAT PANEL UNTUK MENINGKATKAN PEMAHAMAN KONSEP BILANGAN ANAK USIA 5–6 TAHUN - Betty Setyawati; Syahrul Ismet (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
To enhance children’s basic skills—particularly cognitive skills—AUD education is essential. When children aged five to six enter elementary school, understanding number concepts becomes one of the most important thinking skills. Number sense encompasses an understanding of one-to-one correspondences, number symbols, and quantity. However, the teaching of number concepts in the classroom is still dominated by static, conventional teaching materials, particularly at the PGRI Bukit Berlian Kindergarten in North Bengkulu. This results in children being less engaged and interested in learning, and they struggle to grasp abstract number concepts. An interactive flat panel (IFP) is a touchscreen with numerous features that allow students and educators to interact with one another. Through activities such as counting and matching, the IFP’s touch-and-drag features help children understand number concepts.